Myeloid autophagy genes protect mice against fatal TNF- and LPS-induced cytokine storm syndromes. Issue 4 (3rd April 2023) - Wang, Ya-Ting; Sansone, Amy; Smirnov, Asya; Stallings, Christina L.; Orvedahl, Anthony
ABSTRACT: Macroautophagy/autophagy regulates inflammation via multiple mechanisms, including lysosomal degradation of specific cellular components. Certain autophagy gene "cassettes" also participate in non-canonical processes to mediate important biological activities. While select autophagy genes in myeloid cells have been implicated in protecting mice in models of cytokine storm syndromes (CSS), a more extensive genetic analysis of the autophagy pathway for this disorder has not been reported to date. We determined that multiple canonical autophagy genes in the myeloid compartment protected against fatal disease from both intravenous TNF and intraperitoneal LPS, with the notable exception that Atg14 was dispensable for the latter. Serum cytokine analyses and genetic crosses further revealed distinct mechanisms contribute to the hypersensitivity of autophagy gene-deficient mice in these CSS models. Surprisingly, TNF was dispensable for the increased mortality of myeloid 5 -deficient mice challenged with LPS. Tissue-specific ablation of Atg5 in cells expressing ITGAX/CD11c and LYZ2/LYSM, but not S100A8/MRP8, defined a myeloid subset that protected against TNF, while protection against LPS was conferred by Atg5 in a distinct subset of LYZ2-expressing cells. Together, this study identifies autophagy gene sets and specific cell types that protect against fatal inflammation due to CSS, highlighting important differences in two commonly used murine models of the disorder. Abbreviations: ATG5: autophagy related 5; ATG7: autophagy related 7; ATG14: autophagy related 14; ATG16L1: autophagy related 16-like 1 (S. cerevisiae); BECN1: beclin 1, autophagy related; CASP1: caspase 1; CASP4/CASP11: caspase 4, apoptosis-related cysteine peptidase; CIM: conditionally immortalized macrophage; CLP: cecal ligation and puncture; CSS: cytokine storm syndrome; DC: dendritic cell; IFNG/IFNγ: interferon gamma; IFNGR1: interferon gamma receptor 1; ip: intraperitoneal; iv: intravenous; IL12/p70: interleukin 12, p70 heterodimer; IL18: Interleukin 18; ITGAX/CD11c: integrin alpha X; LAP: LC3-associated phagocytosis; LPS: lipopolysaccharide; LYZ2/LYSM: lysozyme 2; MAP1LC3A/LC3: microtubule-associated protein 1 light chain 3 alpha; RB1CC1/FIP200: RB1-inducible coiled-coil 1; S100A8/MRP8: S100 calcium binding protein A8 (calgranulin A); TICAM1/TRIF: TIR domain containing adaptor molecule 1; TLR4: toll-like receptor 4; TNF: tumor necrosis factor.